Development of Mathematics Learning Tools Based on Ethnomathematics on Rectangular and Triangles in Junior High School - Winda Gusfitri; Abdurrahman Abdurrahman; Dedek Andrian; Nofriyandi Nofriyandi; Sri Rezeki (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
Ethnomathematics is mathematics that appears in a particular culture and is considered a learning approach that aims to enable students to solve mathematical problems related to their daily activities which include grouping, counting, measuring, designing buildings or tools, playing, and determining location. This study aims to produce ethnomathematics-based mathematics learning tools on quadrilaterals and triangles that have been tested for feasibility. Learning tools are in the form of learning implementation plans (LIP) and student worksheets (SAS). This study uses the R&D method with the following steps: potential and problems, data collection, product design, design validity, design revision, and final product. In the R&D method, researchers did not use the pilot stage because school learning was carried out online. The data collection technique used is validation data and validator response data from two Mathematics Education Lecturers and one Mathematics Teacher. The data analysis technique used is validation data analysis and validator response data analysis to mathematics learning tools. From the research results obtained LIP validation results 89.72% with very valid criteria and 92.25% SAS validation results with very valid criteria. While the results of the validator's response to LIP were 80% with good criteria and the results of the validator's response to SAS were 79.86% with good criteria. Based on these results, it can be concluded that the development of ethnomathematics-based mathematics learning tools on quadrilateral and triangle material is feasible to be used and tested in junior high schools.